Guttate psoriasis is associated with an intermediate phenotype of impaired Langerhans cell migration. (4th August 2014) - Eaton, L.H.; Chularojanamontri, L.; Ali, F.R.; Theodorakopoulou, E.; Dearman, R.J.; Kimber, I.; Griffiths, C.E.M.
Summary Background An episode of guttate psoriasis can be an isolated event, can recur as guttate episodes, or develop into chronic plaque psoriasis (CPP). A previous study revealed that early‐onset (before age 40 years) CPP is associated with inhibition of epidermal Langerhans cell (LC) migration. Objectives To determine whether guttate psoriasis is also associated with abnormal LC mobilization. Methods Three groups of patients were recruited: current guttate episode (n = 5); guttate psoriasis progressed to CPP (n = 6); and resolved guttate psoriasis (n = 2). Biopsies were taken from uninvolved skin and LC migration was measured ex vivo using an epidermal explant model. Results Patients with a current episode of guttate psoriasis displayed epidermal LC migration, although the extent was significantly lower than in skin from healthy controls (P < 0·05). In contrast, in those patients in whom guttate psoriasis developed into CPP there was no mobilization of LC. Finally, in patients in whom guttate psoriasis had resolved, LC migration was normal. Conclusions We have shown that guttate psoriasis is associated with an abnormality of LC mobilization, but a less marked inhibition compared with that seen in CPP. In resolved guttate psoriasis LC function returns to normal. These data provide further evidence that the pathogenesis of psoriasis is characterized by significant changes in epidermal LC function.